Henti.Elak.Basmi.Asap.Tembakau (HEBAT) and stop nicotine addiction among secondary school students (SNAASSS) 2024 - Kanoo, Lina Lohshini; Abdul Razak, Suraya; Md Nasir, Nik Munirah; Miptah, Hayatul Najaa; Ismail, Ilham Ameera; Mat Nasir, Nafiza; Kamaruddin, Khairatul Nainey (Faculty of Medicine, 2024)
In line with Malaysia’s goal of becoming a Smoke-Free Nation by 2040, serious youth advocacy must be initiated and fully implemented. The evidence to support peer-led intervention and advocacy approaches is abundant and highly effective. This approach, with targeted youth advocacy, is key to nurturing a new generation toward a smoke-free and vape-free culture.